The container victory garden : a beginner's guide to growing your own groceries - Stuckey, Maggie (Harper Celebrate, 2023)
"In her trademark warm and informative style, bestselling author and expert gardener Maggie Stuckey shares everything you need to know to succeed with container gardening: planning, gearing up, planting, nurturing, and harvesting"--